The Influence of Financial Performance and Company Size on Firm Value: An Empirical Study on Pharmaceutical Issuers - Sutadipraja, Marista Winanti; Basyir, Ashar; Dewi, Ghina Kemala; Pradita , Afrila Eki; Permanasari, Astried (Forum Kerjasama Pendidikan Tinggi, 2025)
Company value is an important indicator for investors in making decisions. This study aims to determine whether Return on Assets (ROA), Leverage, and Company Size influence Company Value in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The methods used in this study are Multiple Linear Regression Analysis, Descriptive Statistics, Classical Assumption Testing, and Hypothesis Testing. The population in this study was 10 pharmaceutical industry companies, which were then selected into four companies using the Purposive Sampling method. The analytical tool used in this study was the SPSS program. The results show that Return on Assets (ROA) does not significantly influence the company value variable proven with a significant value of 0.967 > 0.05. While Leverage and Company Size have a significant effect on the company value variable. The results of each variable obtained values below 0.05 (0.000 < 0.05) and (0.003 < 0.05). Return on Assets (ROA), Leverage, and Company Size have a simultaneous and significant effect on company value